CRITERIA FOR ASSESSING THE COOPERATION SKILLS OF PRESCHOOL EDUCATIONAL INSTITUTION STAFF BASED ON INNOVATIVE MANAGEMENT METHODS - Khudayberdiyeva Dilafruz Abidovna; Ziyamova Madina Jakhongir qizi (Web of Journals Publishing, 2026)
In contemporary society, the requirements for preschool education institutions are steadily increasing, which necessitates the implementation of innovative management methods not only to enhance the quality of education but also to foster effective cooperation among staff members. The ability of employees to work collaboratively is among the central factors determining the successful realization of educational goals and the positive development of children within an educational setting. Therefore, there is a pressing need to establish clear, measurable criteria for assessing the cooperation skills of preschool institution staff, particularly with consideration for innovative management approaches.
Keywords: Innovative management, preschool education, teamwork assessment, collaboration skills, evaluation criteria, staff development, professional competence, early childhood institutions, cooperative learning, performance indicators.